Die AfD in den Medien Eine Framing-Analyse der Partei am Beispiel politischer Talkshows - Heyen, Sonja (Schriftenreihe Medienrecht & Medientheorie, 2020)
"Purpose - This master thesis examines the influence of political framing by the German party 'Alternative für Deutschland' (AfD) on the medial debate as a contemporary issue. Approach - Based on the concept of framing, public broadcast talk shows about the German regional elections in autumn 2019 were analysed regarding their handling of strategic political frames. By comparing the results of this content analysis with a subsequent examination of follow-up communication among selected key online-media, conclusions about the influence of political framing on the medial debate were drawn. Findings - In accordance with the findings, a distinctive transfer of strategic framing is delivered throughout the analysed media coverage, focussing on the polarising issue of how to politically classify the AfD. Practical Implications - The ascertained orientation in journalistic framing was criticised and recommendations towards a recollection of journalistic standards were given."